(untitled) (Journal of Atomic and Molecular Sciences, 2016)
In this paper, the non-Markovian transfer tensor method (TTM) suggested by Cao's group was utilized in a real chemical reaction in liquids from a classical point of view. From the results of this numerical simulation, dramatic enhancement in speed of calculations and decrease in computational cost are shown by applying TTM method. It is wise to be used in complex systems with lots of degrees, such as the process of protein folding or in treating propagations with mountains of data. For some specific quantities we are interested in, how to find a map from complex systems to simple ones and from huge freedoms to a few ones, such as just to one freedom in this paper, it remains something for us to do in the future.